Empowering women entrepreneurs in Malaysia: Key success factors and challenges - Ahamat, Amiruddin; Aris, Amir; Mohd. Yusof, Sitinor Wardatulaina; Wahid, Mansor Shah (UUM PRESS, 2026)
This study investigates the factors contributing to the success of women entrepreneurs in Malaysia. Its aim is also to enhance our understanding of the role of these factors in economic development. Utilizing a qualitative case study approach, the research examines the experiences of Malaysian women entrepreneurs from diverse backgrounds. Data were collected through interviews and analyzed using descriptive and content analysis methodologies. The findings indicate that external factors, such as limited educational background and poor time management, serve as key motivators. Critical success factors include leadership styles and entrepreneurial skills that enhance competitiveness. The study has been able to contribute theoretically by offering insights into the unique challenges and success drivers of female entrepreneurs in Malaysia, and practically by informing policies and support mechanisms to boost women’s entrepreneurial success and its sustainability. It underscores the importance of family and social support, business networks, and government interventions in fostering a supportive environment for women entrepreneurs. The study advocates for targeted interventions to address specific needs, including enhanced access to finance, training, and business networks, to ensure the sustained success of women entrepreneurs in Malaysia.